A clinico-radiological study of mild traumatic brain injury using the national emergency x-radiation utilization study decision instrument - Shingada, Krupa V.; Litake, Manjusha M.; Tilak, Kedar M. (International Journal of Research in Medical Sciences, 2019)
Background: While traumatic Brain Injury (TBI) is one of the leading causes of morbidity and mortality in the Indian subcontinent, little is known regarding its basic characteristics. While CT scanning plays an important role in primary assessment of TBI, it is not always indicated in cases of mild TBI. Thus, the present study was carried out to describe the characteristics of cases of mild TBI presenting to a tertiary care hospital in India and determine the need for CT scanning in them using the National Emergency X-radiation Utilization Study (NEXUS) decision instrument. Methods: In this prospective study, a detailed history was obtained, and clinical examination performed for each patient, followed by calculation of the NEXUS score. CT scan findings were recorded. Outcome measures were safe discharge, need for neurosurgical intervention or death. Results: Out of the 425 patients, 87.05% were males. Road Traffic Accident (RTA) was the most common mode of injury. 206 patients had significant intracranial injuries, with skull fractures and hemorrhagic contusions being the most common.138 out of these 206 had a positive NEXUS score. ENT bleed and history of loss of consciousness were also found to be important predictors of significant intracranial injuries. 83 patients were discharged safely from the emergency department, 14 required neurosurgical intervention and 2 died during the course of their stay in the hospital. Conclusions: NEXUS decision instrument can be a useful tool to determine the need for CT scanning in patients of mild TBI.